Ethnocentrism in Multinational Corporations: A Bibliometric Mapping of Cross-Cultural Management and Workforce Diversity Studies - Qristin Violinda; Rr. Hawik Ervina; Bayu Kurniawan; Chadyan Faturohman (Proceeding of The International Conference on Business and Economics, 2026)
This study explores the intellectual structure and research trends surrounding ethnocentrism in multinational corporations (MNCs) through a bibliometric mapping approach, with particular attention to cross-cultural management and workforce diversity studies. An initial dataset of 200 records was retrieved using Publish or Perish from Google Scholar and Crossref, of which 96 peer-reviewed journal articles published between 2020 and 2025 were retained following a PRISMA guided screening process. Bibliometric analysis was conducted using VOSviewer to examine keyword co occurrence, network relationships, and thematic density. The results indicate that ethnocentrism functions as a central organizing concept within the literature, closely associated with cultural differences, expatriation, workforce diversity, and organizational practices in multinational contexts. Temporal patterns observed in overlay and density visualizations suggest a growing scholarly emphasis on practice-oriented and context-specific perspectives, particularly in relation to managerial and organizational implications in global operations. Overall, this study offers a structured synthesis of existing research, highlights emerging thematic directions, and provides a foundation for future empirical and comparative inquiries into cultural diversity management in multinational corporations.